HUBUNGAN ANTARA PENGETAHUAN, SIKAP IBU DAN ASUPAN MAKANAN PENDAMPING ASI DENGAN STATUS GIZI BALITA USIA 12-24 BULAN DI WILAYAH ATAS PUSKESMAS PEJAWARAN BANJARNEGARA - Ratih Pranawinarni; Sunarto Sunarto; Dyah Nur Subandriani (Poltekkes Kemenkes Semarang, 2017)
Background: Riskesdas 2007, 2010 and 2013 show the prevalence of malnutrition in a row at 18.4%, and 17.9% and 19.6% of. Mother's attitude, knowledge and intake of less is the cause of the problem of malnutrition.Objective: to Determine the relationship of knowledge, attitude of the mother and the intake of complementary foods and nutritional status of children age 12 – 24 months in the region on Phc Pejawaran.Methods: Type of observational analytic study design case-control. Study subjects all children under five underweight, as a control toddler good nutrition with metching sexes, taken at random. Bivariate analysis using Mc Nemar with α ≤ 0.05. Method of sampling begins with the screening, the nutritional status based on the index of BB/U, the nutritional intake with recall interview 2 x 24 hours. Knowledge and attitude with interview using questionnaire instruments.Results : case group mothers less knowledge 41%, the attitude is not supportive of 12.5%, the energy intake is not enough to 43.7% and protein of 39.6%. The control group maternal knowledge less at 35.4% , the attitude is not supportive 8% , the energy intake is not enough to 37.8 and protein 35,5% .Conclusion: There is no significant influence between knowledge (p=0,508), attitude (p=0,727), energy intake (p=0,508) and protein (p=0.754 to) with the nutritional status of children aged 12-24 in the region above the public health center Pejawaran Banjarnegara.Suggestion: Need to increase counseling on mother and toddlers to improve knowledge and attitudes to prevent the toddler is underweight.